Successful Management of Metastatic Eccrine Porocarcinoma. (26th October 2013) - Aaribi, Imane; Mohtaram, Amina; Ben Ameur El Youbi, Meryam; Kharmoum, Jinane; El Kabous, Mustapha; Mrabti, Hind; El Khannoussi, Basma; Errihani, Hassan
Abstract : Eccrine porocarcinoma (EPC) is a rare tumor. It develops from the intraepidermal ductal portion of the eccrine sweat gland. Metastatic disease is rare. We report a new case of metastatic eccrine porocarcinoma with a successful management and a good response to docetaxel. A 54-year-old man was admitted with a mass in the breast. Biopsy specimen found carcinomatous tumor proliferation with large anastomosing ducts. Cellular atypia were noted, with eosinophilic cytoplasm and round to oval nuclei. The tumor showed positive immunoreactivity for ACE and negative to anti-PS-100. Resection was performed. One year later, he presented with local and metastatic recurrences. The patient had received 3 cycles of cisplatin and 5-fluorouracil; he progressed with increase in mass size and number of lung lesions. He has been undergoing three cycles of docetaxel with complete response in the lung and regression of the breast mass. The mass was excised. Porocarcinoma is a very rare entity and poorly understood. In the metastatic phase, it has modest or no sensitivity to anticancer treatment. Docetaxel should be considered in the metastatic eccrine porocarcinoma.